Explaining differences in flood management approaches in Europe and in the USA – a comparative analysis. Issue 4 (28th April 2015) - Bubeck, P.; Kreibich, H.; Penning‐Rowsell, E.C.; Botzen, W.J.W.; de Moel, H.; Klijn, F.
Abstract: Flood risk management in Europe and worldwide is not static but constantly in a state of flux. There has been a trend towards more integrated flood risk management in many countries. However, the initial situation and the pace and direction of change is very different in the various countries. In this paper, we will present a conceptual framework that seeks to explain why countries opt for different flood risk management portfolios. The developed framework utilises insights from a range of policy science concepts in an integrated way and considers, among others, factors such as geographical characteristics, the experience with flood disasters, as well as human behavioural aspects.